DIAGNOSIS DAN INSIDENSI PENYAKIT REBAH KECAMBAH PADA TANAMAN KACANG TANAH (Arachis hypogaea) DI KABUPATEN MINAHASA - Elisca A. Bullele; Max M. Ratulangi; Guntur S.J. Manengkey; Henny V.G. Makal (Universitas Sam Ratulangi, 2015)
This study aims to determine the incidence of disease diagnosis and plant pests on crops peanut held in Minahasa District, in the district of the village Kawangkoan Kanonang, villages and rural Kiawa Tombasian. In the District of Sonder held in the village Leilem I, villages and rural Talikuran Leilem II, which took place during the months of September to December 2013. The study continued in the Laboratory of Microbiology and Plant Pathology, Faculty of Agriculture, University of Sam Ratulangi to observe microscopic plant pests that cause disease in plants peanuts. The method used is a survey method by determining the location and observation blocks. Location observation peanut farmer's crop in the district and sub-district Kawangkoan Sonder. Each village in each district specified area is used as an observation area, which is 10m x 20m which is divided into five sub-plot of the observations in the form of diagonal slices. Observations plant started in germination phase performed 4 times at intervals of one week. Plants showing symptoms of the disease-causing Aspergillus flavus which can be seen on the trunk of peanut plants were starting to rot and colored black and attack the plant until it withered and stunted. Pathogens infect the plant at the time of germination. The incidence of plant pests on crop diseases peanut in Minahasa highest average occurred in the village Kanonang with an average of 8.49%, Kiawa village with an average of 7.70% later in the village Leilem I with an average of 7.54 %, on average Tombasian villages of 7.31%, with an average Talikuran 7.21 and terenda with an average 6.73%. The incidence of plant pests diseases in the district and sub-district Kawangkoan Sonder at all observation sites every week by plant pests incidence of disease caused by the fungal pathogen is with an average of 8.49% and a low of 6.73% attack.